Their eyes were watching God - Hurston, Zora Neale (University of Illinois Press, 1991)
Fair and long-legged, independent and articulate, Janie Crawford sets out to be her own person--no mean feat for a black woman in the '30s. Janie's quest for identity takes her through three marriages and into a journey back to her roots.